Supraclavicular Approach of Lobectomy Improves Quality of Life for Patients With Unilateral Papillary Thyroid Microcarcinoma: A Prospective Cohort Study - Xue, Shuai; Wang, Qiuli; Chen, Guang; Wang, Peisong; Zhang, Li (Frontiers in Endocrinology, 2022)
Objective Postoperative neck symptoms, including pain, swelling, uncomfortable feelings during swallowing, and incision adhesion formation, are common in patients after lobectomy through the traditional middle neck approach. A new unilateral supraclavicular approach is proposed to protect the anterior cervical region and reduce related complications. The aim of this study is to investigate the efficacy, safety, and advantages of the supraclavicular approach in lobectomy for unilateral papillary thyroid microcarcinoma (PTMC). Methods Two hundred sixty-three patients were recruited into either a conventional middle group (CM) or a new supraclavicular (NS) group. Clinicopathological features, surgically related variables, and postoperative symptoms were recorded. Quality of life (QOL) of all patients was assessed by the 12-item short-form health survey (SF-12) and thyroid cancer-specific QOL (THYCA-QoL) questionnaire in 3 and 12 months. Results There were no statistically significant differences in clinicopathological features (including sex, age, multifocality, extrathyroidal extension, histological variants, largest tumor diameter, Hashimoto’s thyroiditis, metastasized central lymph node, removed central lymph node, surgeon, BRAF mutation, and follow-up duration), hospitalization (including hospital cost, surgery time, and blood loss during surgery), and complications between the two groups. Patients who underwent lobectomy through the NS approach had significantly better SF-12 physical, mental, and THYCA-QoL than the CM group patients in both 3 and 12 months (all p < 0.001). Moreover, the NS group had a shorter hospitalization time. Conclusion In conclusion, the NS approach for lobectomy is a safe and effective method for reducing postoperative symptoms and increasing QOL in patients with unilateral PTMC in both 3 and 12 months’ follow-up.